Burkholderia pseudomallei Infection in a Cystic Fibrosis Patient from the Caribbean: A Case Report - Dimas Mateos Corral; Allan L Coates; Yvonne CW Yau; Raymond Tellier; Mindy Glass; Steven M Jones; Valerie J Waters (Canadian Respiratory Journal)
Burkholderia pseudomallei is a pathogen identified with increasing frequency in the respiratory tracts of cystic fibrosis (CF) patients from endemic areas such as Southeast Asia and northern Australia. The following report describes the first known reported case in a CF patient from the Caribbean attending a North American CF clinic.